UANG DAN NILAI WAKTU UANG DALAM ISLAM - YUNIDA EEN PRIYANTI (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2017)
Money is something that is generally accepted as means of payment in a particularregion or as a means of repayment of debt or as a tool to make purchases of goods andservices. Money is the blood of the economy, because in modern society the economicmechanism based on the traffic of goods and services. In conventional economics andeconomic system of Islam there are similarities and differences in view or define money.In an Islamic economy will not happen the concept of time value of money as in theconventional economy; in Islamic money only as a means of trade; Islam considers thatmoney and commodities are different where money has no intrinsic usefulness, can notbe used directly to meet human needs; as well as the money does not have a time valuebut the time may have economic value depends on how the user. Time will haveeconomy value if the time is used well and wisely.